Analisis Kualitas Layanan kepada Konsumen di Nocturnal Coffee Bali dengan menggunakan Metode Model Kano - Surya, Indah; Wiranatha, A. A. P. Agung Suryawan; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): Desember, 2020)
Nocturnal Coffee Bali is one of the actors in the culinary business that can maintain the quality of service to customer satisfaction so that the unterests customers do not decrease. The purpose of this study was measurement the level of customer satisfaction from the result of the actual performance gap attribute with customer expectations so that it will be know how much the level of service satisfaction has been provided to customers and provide solutions for improvement. Service Quality and the Kano method were the methods used in this study. The result was obtained in this study were in Kano for the Must-be category on the attribute "Adequate parking space" with a gap score of -1.84. In the One-dimensional category on the attribute "Patience and calmness of employees in serving customers" with a gap score of -0.44. For the Attractive category on the attribute "Employees are willing to help consumers if needed" with a gap score of -0.44. Keywords : Quality of service, customer satisfaction, service quality, kano method.